2018
DOI: 10.14814/phy2.13742
|View full text |Cite
|
Sign up to set email alerts
|

Sympatho-excitatory response to pulmonary chemosensitive spinal afferent activation in anesthetized, vagotomized rats

Abstract: The sensory innervation of the lung is well known to be innervated by nerve fibers of both vagal and sympathetic origin. Although the vagal afferent innervation of the lung has been well characterized, less is known about physiological effects mediated by spinal sympathetic afferent fibers. We hypothesized that activation of sympathetic spinal afferent nerve fibers of the lung would result in an excitatory pressor reflex, similar to that previously characterized in the heart. In this study, we evaluated change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…recently demonstrated a sympathetic pressor reflex response that was elicited by application of capsaicin to the visceral pleura surface of the lungs or into the primary bronchus in vagotomized rats, clearly pointing to an involvement of stimulation of TRPV1 receptors expressed in the sympathetic spinal pulmonary afferents (Shanks et al . ). Whether and to what extent this reflex mechanism plays a part in the SO 2 ‐induced increase in ABP observed in this study remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…recently demonstrated a sympathetic pressor reflex response that was elicited by application of capsaicin to the visceral pleura surface of the lungs or into the primary bronchus in vagotomized rats, clearly pointing to an involvement of stimulation of TRPV1 receptors expressed in the sympathetic spinal pulmonary afferents (Shanks et al . ). Whether and to what extent this reflex mechanism plays a part in the SO 2 ‐induced increase in ABP observed in this study remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…In a pilot experiment, the upper thoracic spinal afferents were ablated by epidural application of RTX as previously described. 11 Briefly, rats were anesthetized using 2%-3% isoflurane:oxygen mixture. Rats were placed in the prone position and a small midline incision was made in the region of the T13-L1 thoracic vertebrae.…”
Section: Epidural Application Of Rtxmentioning
confidence: 99%
“…8,9 On the other hand, activation of spinal afferents tends to be sympathoexcitatory and pro-inflammatory. [10][11][12][13][14][15] It is well known that small diameter spinal Transient Receptor Vanilloid 1 (TRPV1)-positive afferent c-fibers contain neuropeptides such as substance P (SP) and calcitonin gene related peptide (CGRP). 16 These peptides tend to dilate adjacent vasculature and increase microvascular permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Using an experimental design similar to CSAR activation, we recently demonstrated that topical application of bradykinin and capsaicin directly to the lung visceral pleura results in a sympathetic reflex in anesthetized, vagotomized, open-chested rats (33). This reflex, to the best of our knowledge previously undescribed, includes increases in MAP, HR, and RSNA (33). We named this reflex the pulmonary spinal afferent reflex (PSAR).…”
Section: Introductionmentioning
confidence: 99%
“…We named this reflex the pulmonary spinal afferent reflex (PSAR). We know that both the PSAR and CSAR originate at the level of T1ϪT4 DRG, which provide sensory afferent innervation to the heart and lung, because chemical denervation of T1ϪT4 DRG sensory afferents with the potent neurotoxin resiniferatoxin abolishes both reflexes (33,49). However, whether pulmonary spinal sensory afferents are also sensitive to TRPA1 receptor agonists remains unknown.…”
Section: Introductionmentioning
confidence: 99%